Evaluation of Variability in Resting Energy Expenditure and Its Relationship with Macronutrients and Gestational Weight Gain During the Second Trimester of Pregnancy (P11-136-19). (13th June 2019) - Wyst, Kiley Vander; Buman, Matthew; Shaibi, Gabriel; Petrov, Megan; Reifsnider, Elizabeth; Whisner, Corrie
Abstract: Objectives: Resting energy expenditure (REE) comprises 60% of total energy expenditure and variations may be associated with gestational weight gain (GWG). There is a paucity of research investigating the relationship between REE and GWG. We investigated variations in REE and dietary composition throughout the second trimester and their association with GWG. Methods: In this controlled trial, pregnant women (N = 16, mean age of 29.9 ± 4.3 years) with a gestational age < 17 weeks used the Breezing™ device for 13 weeks. This device is a real-time metabolism tracker that measures REE via indirect calorimetry. Height, weight, REE, and dietary intake via 24-hr recall were assessed every 2 weeks. Rate of GWG was calculated as weight gain divided by number of study weeks. Early (EC, GA wks 14–21), late (LC, GA wks 21–28), and overall (OC, GA wks 14–28) changes in macronutrient composition, REE, and GWG were used to evaluate time-specific associations. Group differences were analyzed using a General Linear Model in SPSS Version 25. Results: Among the 16 participants, 25% of women were normal weight, 50% were overweight, and 25% were obese at study start. Women had a total and rate of GWG of 8.1 ± 2.9 kg and 0.6 ± 0.2 kg/wk, respectively. REE increased 72 ± 211 kcals/d during the early period, 121 ± 294 kcals/d during the late period, and 200 ± 316 kcals/d overall (from 1544 ± 237 kcal/d to 1744 ± 384 kcal/d). Early changes in REE were significantly correlated with the late changes in total ( r = 0.52, P = 0.04) and rate of weight gain ( r = 0.54, P = 0.03). A correlation between overall changes in REE and total weight gain was moderate and approached significance, r = 0.44, P = 0.09. Changes in total energy, fat, carbohydrate, and protein intake were not correlated with changes in REE; however, a moderate relationship between early changes in REE and overall changes in energy intake approached significance, r = 0.46, P = 0.07. Changes in GWG and REE did not differ among normal, overweight, or obese women (EC: F(2, 15) = 0.36, P = 0.70; LC: F(2, 15) = 2.37, P = 0.13; OC: F(2.15) = 1.27, P = 0.31). Conclusions: Early changes in REE demonstrated a moderate, positive correlation with total and rate of GWG suggesting that assessment of REE early in pregnancy may help understand changes in GWG. Future research that evaluates both REE and dietary composition throughout pregnancy may provide insight into appropriate GWG. Funding Sources: Project HoneyBee, Arizona State University.